SUBSTANTIATION OF RURAL DEVELOPMENT EVALUATION METHODOLOGY PROCEDURE - Сава, А. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The application of methodological approaches for the study of economic; social and environmental processes in rural areas; assessment of their status for all components of sustainable development elements; the choice of methods and sequence of research stages are important the premises of their development strategy The purpose of this article leis in scientific substantiation of methodological principles and procedural elements of rural areas development evaluation. To achieve this goal such methods of scientific research as the dialectical method of economic laws knowledge; systematic approach to economic phenomena studying; as well as monographic; abstract-logical and abstraction methods.are used. The article substantiates the scientific research methodology on the development of rural areas;the essence rural areas socio-economic situation evaluation technology is develope; the research empirical part stages of rural areas development and their evaluation are defined. Promising directions for further research are modern approaches studying and application in substantiation of rural areas socio-economic development in practice.